2021
DOI: 10.1007/s11657-021-00978-7
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of and risk factors for hip fracture in Nagasaki, Japan from 2005 to 2014

Abstract: Summary The annual incidence of new hip fractures increased from 2005 to 2014 in Nagasaki and females were much more affected. High-risk factors were identified as age ≥ 80 years, winter, indoors, living room, Monday, and early morning. Seven days after admission, most patients remained hospitalized and had been treated surgically. Introduction Hip fractures are major osteoporotic fractures that reduce quality of life. In Japan, the incidence of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…In this study, the human femoral neck samples that we collected were predominantly female, consistent with the higher prevalence of OA and fractures in females [ 20 , 21 ]. In addition, no significant differences in the age and body mass index were observed between the OA and fracture (normal for cartilage) groups for all of the experiments in which the gene expression was analyzed, such as human primary cultured chondrocytes and cartilage.…”
Section: Discussionmentioning
confidence: 54%
“…In this study, the human femoral neck samples that we collected were predominantly female, consistent with the higher prevalence of OA and fractures in females [ 20 , 21 ]. In addition, no significant differences in the age and body mass index were observed between the OA and fracture (normal for cartilage) groups for all of the experiments in which the gene expression was analyzed, such as human primary cultured chondrocytes and cartilage.…”
Section: Discussionmentioning
confidence: 54%
“…Hagino et al also reported that the incidence of hip fractures in Tottori Prefecture increased until 2018 for males, whereas it did not increase after 2010 for females [ 34 ]. While some reports, such as these, show that the incidence of hip fractures did not increase, most reports indicate that the incidence of hip fractures continues to increase [ 7 , 35 , 36 ]. The incidence of hip fractures in Niigata Prefecture increased for both males and females from 1985 to 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Hip fracture is a serious complication of osteoporosis and is a major problem worldwide [39]. Consistently documented demographic risk factors include older age, female sex, low bone mass, low body weight, estrogen deficiency, tendency to fall, disability, smoking, chronic alcoholism, diabetes mellitus, and insufficient sunlight exposure [40]. Medications that have been significantly associated with hip fracture include antidepressants, antiparkinsonian drugs, antipsychotic drugs, anxiolytic drugs, benzodiazepines, systemic corticosteroids, H2 antagonists, proton pump inhibitors, and thyroid hormone [41].…”
Section: Discussionmentioning
confidence: 99%